Isotope record in a stalagmite from northeastern India through the last deglaciation - Franziska A Lechleitner; Sebastian F M Breitenbach; Hai Cheng; Birgit Plessen; Kira Rehfeld; Bedartha Goswami; Norbert Marwan; Denize Eroglu; Jess F Adkins; Gerald H Haug (PANGAEA, 2017)
Northeastern (NE) India experiences extraordinarily pronounced seasonal climate, governed by the Indian summer monsoon (ISM). The vulnerability of this region to floods and droughts calls for detailed and highly resolved paleoclimate reconstructions to assess the recurrence rate and driving factors of ISM changes. We use stable oxygen and carbon isotope ratios (d18O and d13C) from stalagmite MAW-6 from Mawmluh Cave to infer climate and environmental conditions in NE India over the last deglaciation (16-6ka). We interpret stalagmite d18O as reflecting ISM strength, whereas d13C appears to be driven by local hydroclimate conditions. Pronounced shifts in ISM strength over the deglaciation are apparent from the d18O record, similarly to other records from monsoonal Asia. The ISM is weaker during the late glacial (LG) period and the Younger Dryas, and stronger during the Bølling-Allerød and Holocene. Local conditions inferred from the d13C record appear to have changed less substantially over time, possibly related to the masking effect of changing precipitation seasonality. Time series analysis of the d18O record reveals more chaotic conditions during the late glacial and higher predictability during the Holocene, likely related to the strengthening of the seasonal recurrence of the ISM with the onset of the Holocene.
Supplement to: Lechleitner, FA et al. (2017): Climatic and in-cave influences on d18O and d13C in a stalagmite from northeastern India through the last deglaciation. Quaternary Research, 88(03), 458-471, https://doi.org/10.1017/qua.2017.72